THE ROLE OF PARENTS IN PALACIO’S WONER - Sipasi, Sriwindi; Mogea, Tini; Wuntu, Ceisy N (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The aim of this study to reveal the role of parents in palacio’s wonder and to find out the impacts of role parents. The writer use qualitative research in conducting this research. The writer classified the sources of the data into two categories: they are primary and the secondary sources. The primary source is the novel entitled wonder by R.J. Palacio and the secondary sources are taken from some books, articles, dictionaries, and internet data that related to the topic. This study used objective approach the result of this research shows roles of parents and the impacts of parents’ role. The role of parents included nurturing, parenting and educating. The impacts of parents’ role are being a courageous person, becoming a clever child and being a good person